Knygos ekranuose: Švedijos elektroninių knygų rinkos žaidėjai - Krauls-Ward, Ineta (Knygotyra, 2018)
BERGSTRÖM, ANNIKA; HÖGLUND, LARS; MACEVICIUTE, ELENA; NILSSON, SKANS KERSTI; WALLIN, BIRGITTA; WILSON, THOMAS D. BOOKS ON SCREENS: PLAYERS IN THE SWEDISH E-BOOK MARKET. GÖTEBORG: NORDICOM, 2017. 238 P. ISBN 978-91-87957-69-7.